Perakensol: a phenanthrenoid isolated from Aseodaphne perakensis - Mahmud, Zurinah; Khan, Mohammad N.; Lajis, Nordin H.; Tola, Robert F. (American Chemical Society (ACS), 1992)
A new non-alkaloidal minor constituent, perakensol [1], has been isolated from Alseodaphne perakensis.